"Forgetting Ntaba kaNdoda" : reciting performative memories at the Ntaba kaNdoda Monument - Mama, Luthando Vukile James (Rhodes University, Faculty of Humanities, Department of Fine Art, 2018)
"Forgetting Ntaba kaNdoda" : Reciting Performative Memories at the Ntaba kaNdoda Monument serves as a theoretical examination of the Ntaba kaNdoda Monument as a commemorative marker. My mini-thesis unpacks the notions of memory and performative memorialisation at a nationalist memorial in the former Ciskei by examining the concepts of place, memory and memorialisation, which are theoretically integral in my professional practice. This research initiates an investigation into the effects on memory in a situation where the construction of the Monument disrupted an efficacious memorialisation by the communities of Ntaba kaNdoda. In my accompanying MFA exhibition Forgetting Ntaba kaNdoda, I explore notions of place, memory and memorialisation through installations of a variety of photographic processes that are based on what I call 'de-monumental' and performative monuments (Widrich2014). The written component of my MFA submission relates directly to my professional art practice, developing and situating it within a relevant context. In my mini-thesis, I consider photographers working with notions of place, memory and memorialisation. Lebohang Kganye and Nassim Rouchiche's works retrace and recall past memory in the present, while David Goldblatt and Cedric Nunn, who have photographed the Ntaba kaNdoda Monument, point the viewer to the values and histories of the communities most affected by colonialism and apartheid. These photographers' works operate as mnemonic devices that seek to translate a lived experience at a particular place. I use Widrich's (2009; 2014) conception of "performative monuments" , Lippard's (1997) "sense of place" and Nora's (1989) "lieu[x] de mémoire" and "milieux de mémoire" in approaching my professional art practice and my research into the Ntaba kaNdoda memorial. Using these entwining nodes of theories in formulating what I term 'demonumentalisation' in my photography practice at the Ntaba kaNdoda Monument, my photography functions as both performative memorialisation and de-monumentalisation. Remembrance, using photography as a vehicle to represent this notion at Ntaba kaNdoda, transcends the materiality of the Monument. My exhibition, in conjunction with this mini-thesis, therefore reframes and reconfigures theNtaba kaNdoda Monument as a multiplex memory place.
Keywords: Memorialization; Collective memory in art; Memorials in art; Memorials -- South Africa -- Dimbaza; Imperialism in art; Ntaba kaNdoda Monument (Dimbaza, -- South Africa)